1978
DOI: 10.1152/jappl.1978.45.4.574
|View full text |Cite
|
Sign up to set email alerts
|

Role of cardiac output in the pressor responses to graded muscle ischemia in man

Abstract: Ten men repeatedly performed leg exercise (100-150 W) for 7 min with 30-min recovery periods interspersed. Both legs were made ischemic by total occlusion (OCCL), first for 3 min immediately after exercise and second for 30 s before exercise ended and 3 min into recovery. In addition legs were occluded for 3 min at rest (seated). OCCL at rest increased mean arterial pressure (MAP) by 9 Torr but did not affect cardiac output (CO) or heart rate (HR). OCCL at the end of exercise significantly raised MAP and HR ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1
3

Year Published

1980
1980
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 0 publications
5
41
1
3
Order By: Relevance
“…The conflicting results of the present study and those from Farquhar and colleagues is potentially due to differences in exercise intensity and the muscle group, in which the reflex was evoked. For example, CO responses are often seen during PEMI following more intense exercise with a large muscle group, whereas with PEMI following lower-intensity exercise with smaller muscle groups, the pressor response usually occurs primarily via peripheral vasoconstriction (8,16,18,55). In our model, we robustly activated the metaboreflex by inducing hindlimb ischemia in an exercise workload, wherein hindlimb blood flow constitutes about 10% of cardiac output, whereas Farquhar and colleagues (20,25) elicited the reflex from one arm after 30 -40% MVC static contractions.…”
Section: Discussionmentioning
confidence: 99%
“…The conflicting results of the present study and those from Farquhar and colleagues is potentially due to differences in exercise intensity and the muscle group, in which the reflex was evoked. For example, CO responses are often seen during PEMI following more intense exercise with a large muscle group, whereas with PEMI following lower-intensity exercise with smaller muscle groups, the pressor response usually occurs primarily via peripheral vasoconstriction (8,16,18,55). In our model, we robustly activated the metaboreflex by inducing hindlimb ischemia in an exercise workload, wherein hindlimb blood flow constitutes about 10% of cardiac output, whereas Farquhar and colleagues (20,25) elicited the reflex from one arm after 30 -40% MVC static contractions.…”
Section: Discussionmentioning
confidence: 99%
“…This additional test aimed at verifying whether or not this condition "per se" could affect hemodynamics in heart failure patients, even though we as well as others (5,11,12) have demonstrated that, in normal individuals, RCO that was not preceded by exercise was incapable of eliciting any substantial hemodynamic modifications. On a day following the PEMI and CER tests, a RCO session consisting of 12 min (i.e., the same duration as the PEMI and CER tests) was applied: after 6 min of resting, 3 min of regional circulatory occlusion of the arm was applied followed by 3 more min of rest.…”
Section: Methodsmentioning
confidence: 99%
“…The muscle ''metaboreflex'', a reflex evoked by those afferent nerve endings sensitive to accumulation of muscle metabolic end-products, is attracting growing interest in the scientific community because it is thought to contribute significantly to cardiovascular regulation during exercise by providing continuous feedback to the cardiovascular control areas about the metabolic status of contracting muscles [4,26,30,31,35,36].…”
Section: Introductionmentioning
confidence: 99%